A Rare Case of Signet Ring Cell Carcinoma Arising on Duodenal Brunner's Gland Hyperplasia Successfully Treated Via Endoscopic Resection - Hae Rin Lee; Bong Eun Lee; Kyung Bin Kim; Gwang Ha Kim; Moon Won Lee; Dong Chan Joo (Yong Chan Lee, 2024)
Signet-ring cell carcinoma (SRCC) is a rare tumor that most commonly occurs in the stomach. Duodenal SRCCs are extremely uncommon and account for approximately 1% of duodenal adenocarcinomas. Although Brunner's gland hyperplasia (BGH) is a benign duodenal condition, studies have reported several cases of adenocarcinoma originating in an area of BGH. We report a rare case of early-stage SRCC originating in an area of BGH that was successfully treated using endoscopic mucosal resection. Based on the mucin phenotype observed in this case, it is reasonable to conclude that SRCC originated from gastric metaplasia in the area of BGH. Although BGH is a benign condition, careful evaluation is warranted for early detection of combined neoplasms.